Mastering the rules of competitive strategy : a resource guide for managers - Paley, Norton (Auerbach Publications, 2008)
Organized to blend selected historical lessons with modern business practice, this book provides a platform for understanding, developing, and applying competitive business strategies. It guides readers through strategic thinking processes and demonstrates how to apply them when fighting competitive battles.